An ninh dữ liệu và an ninh các mạng LAN - Nam, Phương Minh (Journal of Computer Science and Cybernetics, 2016)
Data security is always a big problem in a very large distributed database. Based on to urgent requirements of  practical applications we proposed s systematical solution to establish a hierarchical security systems for very large persons management database, including electrical signature problem.